2009
DOI: 10.1002/cncr.24303
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of carbonic anhydrase IX expression by cancer‐associated fibroblasts in lung adenocarcinoma

Abstract: The physical aging of the epoxy network consisting of a diglycidyl ether of bisphenol A, m‐xylylenediamine, and polyetherimide was studied by differential scanning calorimetry. The glass transition temperature and the variation of the specific heat capacities have been calculated using the method, based on the intersection of both enthalpy–temperature lines for glassy and liquid states. The apparent activation energy (EH) was calculated using a single method that involved separate temperature and excess enthal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 62 publications
1
25
1
Order By: Relevance
“…Gastric cancer with hypoxic conditions might be associated with more aggressive tumor phenotypes, which may indicate a poorer prognosis for patients. A previous study reported that CA-9 expression by cancer-associated fibroblasts was a better predictor of outcome than that by cancer cells, and provides new insights into the biologic significance of cancer-associated fibroblasts in the hypoxic microenvironment of the lung adenocarcinoma [20]. In our study, however, CA-9 expression by cancer-associated fibroblasts was not a significant predictive marker in 265 cases of gastric cancer (data not shown).…”
Section: Discussioncontrasting
confidence: 54%
“…Gastric cancer with hypoxic conditions might be associated with more aggressive tumor phenotypes, which may indicate a poorer prognosis for patients. A previous study reported that CA-9 expression by cancer-associated fibroblasts was a better predictor of outcome than that by cancer cells, and provides new insights into the biologic significance of cancer-associated fibroblasts in the hypoxic microenvironment of the lung adenocarcinoma [20]. In our study, however, CA-9 expression by cancer-associated fibroblasts was not a significant predictive marker in 265 cases of gastric cancer (data not shown).…”
Section: Discussioncontrasting
confidence: 54%
“…Moreover, the proportion of CAIX-positive stroma cells has been found to differ among BC subtypes [42]. Interestingly, CAIX expression by cancer-associated fibroblasts has been found to be a better predictor of outcome than its expression by cancer cells in patients with lung cancer [43], while in prostate cancer, it has been found to drive epithelial-mesenchymal transition in cancer cells [44].…”
Section: Discussionmentioning
confidence: 97%
“…Other proteins expressed by stromal fibroblasts have been shown to have a prognostic value for solid tumours. In particular, a poor prognosis has been associated with expression in CAFs of p53 tumour suppressor in ductal carcinoma [10], or the hypoxia marker carbonic anidrase IX in human lung adenocarcinoma [11], or periostin in cholangiocarcinoma [12]. On the contrary, the expression of caveolin-1, PTEN or podoplanin in tumour stroma correlates with a favourable prognosis for several cancers [13][14][15].…”
Section: Stromal Reactivity In Cancermentioning
confidence: 96%